2016
DOI: 10.1007/s12035-016-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Circular RNAs and Neurological Disorders

Abstract: Circular RNAs (circRNAs) are a class of long noncoding RNAs that are characterized by the presence of covalently linked ends, and have been found in all life kingdoms. Exciting studies in regulatory roles of circRNAs are emerging. Here we summarize classification, characteristics, biogenesis and regulatory functions of circRNAs. CircRNAs are found to be preferentially expressed along neural genes and in neural tissues. We thus highlight the association of circRNA dysregulation with neurodegenerative diseases s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
123
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 58 publications
(144 reference statements)
0
123
0
1
Order By: Relevance
“…Emerging studies have indicated that circRNAs may play an important role in many diseases, including cancer, diabetes or phlegmonosis . For example, circRNA which derived from the tumor‐suppressor gene Foxo3 has been found to promote cancer cell apoptosis, circZNF292 has been shown to have the property of tumor‐suppressor by negatively regulating progression of cell cycle .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have indicated that circRNAs may play an important role in many diseases, including cancer, diabetes or phlegmonosis . For example, circRNA which derived from the tumor‐suppressor gene Foxo3 has been found to promote cancer cell apoptosis, circZNF292 has been shown to have the property of tumor‐suppressor by negatively regulating progression of cell cycle .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, circRNAs are preferentially expressed in neural tissues along neural genes [18] that are associated with various diseases in the central nervous system (CNS), such as AD, PD and ischaemia [19][20][21]. CircRNA CDR1as, an antisense transcript of CDR1, was reported to be involved with the pathogenesis of PD [20].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of abundant circRNAs in saliva, exosomes and blood samples will make them potential diagnostic or predictive biomarkers for diseases, particularly for cancer development, progression and prognosis. Based on the current knowledge of circular RNAs, these molecules have the potential to be the "next big thing" in the omics research (119–120). …”
Section: Epigenetics and Environmentmentioning
confidence: 99%